2017
DOI: 10.1007/s00198-017-4337-0
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive pulmonary dysfunction is associated with vertebral fractures and bone loss in elderly postmenopausal women

Abstract: Diminished FVC was associated with prevalent vertebral fractures and decreased BMD in Japanese postmenopausal women without apparent pulmonary diseases. Mechanism of such association between pulmonary function and bone status remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Whether this is true in adults who experience permanent vertebral deformity as children merits further study. In the aging, VF contribute to excess mortality (62), and among adult post-menopausal women without a history of pulmonary disease, those with VF had restrictive pulmonary dysfunction compared to those without VF (63). Together, these adult studies suggest that permanent reductions in vertebral height sustained in childhood may have important consequences later in life.…”
Section: Some Children Can Recover From Gio Through Reshaping Of Fracmentioning
confidence: 99%
“…Whether this is true in adults who experience permanent vertebral deformity as children merits further study. In the aging, VF contribute to excess mortality (62), and among adult post-menopausal women without a history of pulmonary disease, those with VF had restrictive pulmonary dysfunction compared to those without VF (63). Together, these adult studies suggest that permanent reductions in vertebral height sustained in childhood may have important consequences later in life.…”
Section: Some Children Can Recover From Gio Through Reshaping Of Fracmentioning
confidence: 99%
“…19,27 Thoracic deformity and pain linked to OVF may compromise respiratory function and balance, increasing the risk of death from respiratory disease or from sustaining an injury such as a hip fracture following a fall. 19,28,29 QoL and excess mortality progressively worsen as the number of OVFs increase.…”
Section: Recruitmentmentioning
confidence: 99%
“…64,70,99,101 In addition, hyperkyphosis and vertebral fracture are associated with compromised respiratory function and this may significantly limit maximal aerobic capacity. 29,81 People in this age group are also likely to have other comorbidities such as cardiovascular disease, which can limit exercise capacity. Considering this, moderate intensity exercise is most appropriate for this population and specific screening for comorbidities and use of the Borg Rating of Perceived Exertion (RPE) scale to guide exercise intensity is recommended.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies investigating the relationship between vertebral fractures and bone mineral density (BMD) in patients with COPD, BMD was not a good predictor of vertebral fracture. Watanabe et al [9] reported that 79.4% had prevalent vertebral fracture whereas only 38.8% had BMD-defined osteoporosis (T≤2.5) in 136 Japanese patients. This result suggested the involvement of BMDindependent mechanisms in COPD patients.…”
Section: Introductionmentioning
confidence: 99%